Religious Education for Muslim Minorities from the Perspective of Taha Jabir al-Alwani - Rizzal Rizqi Apriana; Muhamad Wahyu Fatkur Rohman; Purnomo; Muhammad Faiz Naufal (Islam Transformatif : Journal of Islamic Studies, 2025)
Abstract This study examines the challenges and strategic responses of Islamic religious education among Muslim minority communities in Western societies by focusing on the educational thought of Taha Jabir al-Alwani. Employing a qualitative library-based research approach, the study analyzes both primary and secondary sources related to al-Alwani’s writings on Islamic education and fiqh al-aqalliyyt. The findings reveal that al-Alwani advances a contextual, transformative, and integrative educational model grounded in five core principles: orientation toward maqṣid al-sharīʿah, epistemological renewal (tajdīd), the integration of religious and modern sciences, dialogical pedagogy, and a strong emphasis on ethical formation and social responsibility. Within this framework, Islamic education is conceived not merely as a mechanism for preserving religious identity, but as a means of enabling constructive engagement within pluralistic social settings. The novelty of this study lies in its articulation of the practical relevance of al-Alwani’s educational framework for Muslim minorities in Western contexts, an area that has received limited and unsystematic attention in previous studies. Overall, al-Alwani’s educational thought offers valuable insights for the development of adaptive and future-oriented Islamic education in responding to the challenges of modernity and diversity.   Abstrak Penelitian ini mengkaji tantangan dan strategi pendidikan agama Islam bagi komunitas muslim minoritas di negara-negara Barat dengan menitikberatkan pada pemikiran pendidikan Taha Jabir al-Alwani. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan, dengan menganalisis sumber primer dan sekunder yang berkaitan dengan karya-karya al-Alwani dalam bidang pendidikan Islam dan fiqh al-aqalliyyāt. Hasil penelitian menunjukkan bahwa al-Alwani menawarkan model pendidikan yang kontekstual, transformatif, dan integratif yang dibangun atas lima prinsip utama, yaitu orientasi pada maqṣid al-sharīʿah, pembaruan epistemologis (tajdīd), integrasi ilmu keislaman dan ilmu modern, pedagogi dialogis, serta penekanan pada pembentukan etika dan tanggung jawab sosial. Model ini memposisikan pendidikan Islam tidak hanya sebagai sarana pelestarian identitas keagamaan, tetapi juga sebagai kerangka untuk keterlibatan konstruktif dalam masyarakat yang plural. Kebaruan penelitian ini terletak pada perumusan relevansi praktis kerangka pendidikan al-Alwani bagi Muslim minoritas di konteks Barat, yang selama ini belum banyak dikaji secara sistematis. Secara keseluruhan, pemikiran pendidikan al-Alwani memberikan kontribusi penting bagi pengembangan pendidikan Islam yang adaptif dan berorientasi masa depan dalam merespons tantangan modernitas dan keberagaman.